Postharvest quality of strawberry (Fragaria × ananassa (Duchesne ex Weston) Duchesne ex Rozier) genotypes according to vernalization (2018)
Strawberry production in Paraguay is carried out by small producers, using minimal technology and obtaining low productivity, with the need to expand strawberry genotypes and production techniques. The aim of this study was to evaluate fruit quality of strawberry genotypes according to vernalization. A randomized block design with factorial arrangement 14x2 was performed; factors were genotypes and chilling using 15 plants per treatment and three replicates. Plants were kept in cold room at 5°C, with 8 hours of artificial light and 16 of darkness for a period of 25 days. Five fruits were used per treatment and were evaluated as follows: the amount of total soluble solids, titratable acidity and ratio of total soluble solids to titratable acidity, length/diameter ratio, calyx diameter/fruit diameter ratio, peduncle length and mass loss in postharvest. Data obtained were subjected to analysis of variance simple factorial scheme and averages compared by Tukey test at 5% probability. Vernalization of strawberry plants did not affect fruit shape or total soluble solids content, but increased the percentage of citric acid. Length of peduncle and calix extension had achieved an increasing due to vernalization and decreased postharvest loss of fresh mass, but did not affect fruit preservation at 5°C. Festival and Florida Eliane genotypes may be recommended for in natura consumption and Dover and Oso Grande genotypes for industry.